First, subtract #color(red)(11)# from each side of the equation to isolate the #y# term while keeping the equation balanced:

#-color(red)(11) + 3 + 6x = -color(red)(11) + 11 - 4y#

#-8 + 6x = 0 - 4y#

#-8 + 6x = -4y#

Now, divide each side of the equation by #color(red)(-4)# to solve for #y# while keeping the equation balanced:

#(-8 + 6x)/color(red)(-4) = (-4y)/color(red)(-4)#

#(-8)/color(red)(-4) + (6x)/color(red)(-4) = (color(red)(cancel(color(Black)(-4)))y)/cancel(color(red)(-4))#

#2 - 6/4x = y#

#2 - (2 xx 3)/(2 xx 2)x = y#

#2 - (color(red)(cancel(color(black)(2))) xx 3)/(color(red)(cancel(color(black)(2))) xx 2)x = y#

#2 - 3/2/x = y#

#y = 2 - 3/2x#

Or

#y = -3/2x + 2#